Middle cerebral artery territory infarction in a COVID-19 patient: a case report (Faculty of Medicine Universitas Indonesia, 2021)
Coronavirus disease 2019 (COVID-19) mainly invades the respiratory system, yet previous reports have shown unusual manifestations of COVID-19, including cerebrovascular events. However, detailed case reports are still lacking. A 57-year-old male presented with sudden unconsciousness and right side lateralization for 6 hours before hospital admission. His test results were positive for severe acute respiratory syndrome coronavirus 2 infection. The head computed tomography (CT) scan showed infarction within the middle cerebral artery region. The scan was repeated 48 hours after admission and showed a massive infarct in the left hemisphere with hemorrhagic transformation. A chest CT showed the appearance of bronchopneumonia with ground-glass opacities in both lungs. The patient's condition was rapidly deteriorating, and he died on the third day after admission. Our findings suggest that ischemic vascular events may simultaneously develop due to the progression of COVID-19. A hypercoagulable state and vascular endothelial dysfunction have been proposed as complications of COVID-19 and are risk factors of thrombotic vascular events.